2020
DOI: 10.1002/smi.2905
|View full text |Cite
|
Sign up to set email alerts
|

When empowered nurses are under stress: Understanding the impact on attitudes and behaviours

Abstract: The present study examined the role of stress as a moderator on the indirect effect of structural empowerment, through psychological empowerment, on three important nurse‐related outcomes: affective organizational commitment, nursing workarounds, and safety performance. The results demonstrated that structural empowerment and psychological empowerment were positively related to affective organizational commitment and safety performance, whereas neither were significantly related to nursing workarounds. Consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 77 publications
0
35
0
Order By: Relevance
“…Fevre and colleagues reported that approximately half of the participants in the United Kingdom experienced some forms of unreasonable treatment at work and 40% reported workplace disrespect to be the most common phenomenon [2]. Other studies showed that health sector employees are one of the most vulnerable population to expose to psychosocial risk at work [3]. As previously reported, 65% of nursing professionals in the USA observed lateral violence among co-workers [4].…”
Section: Introductionmentioning
confidence: 99%
“…Fevre and colleagues reported that approximately half of the participants in the United Kingdom experienced some forms of unreasonable treatment at work and 40% reported workplace disrespect to be the most common phenomenon [2]. Other studies showed that health sector employees are one of the most vulnerable population to expose to psychosocial risk at work [3]. As previously reported, 65% of nursing professionals in the USA observed lateral violence among co-workers [4].…”
Section: Introductionmentioning
confidence: 99%
“…Nursing practice workarounds were recognized as common in nursing practice in 8 of 13 studies (62%) 19-21,23,26-29 . A few examples of strategies to decrease/prevent NPWs included new ways to record medical information using software not paper, electronic systems for drug prescription, and pumps that deliver precise medication.…”
Section: Resultsmentioning
confidence: 99%
“…Investigation of medication administration workarounds was the purpose of four of 13 (30%) studies 17,20,23,28 ; while the purpose of the remaining 3 of 13 (23%) studies 18,21,29 examined the influence of stress and professionalism on NPW. Six (46%) studies were qualitative, 21,22,24-26,28 five (38%) quantitative, 17-19,23,29 and two (15%) had a mixed methods designs 20,27 . Overall, all 13 (100%) studies used a diverse group of measures to examine the phenomenon 17-29 …”
Section: Resultsmentioning
confidence: 99%
“…PPE limitations forced the nurses to create workarounds that reflected their ingenuity but also created frustration and stress. This finding is substantiated in a survey of 153 American nurses, which revealed workarounds were highly correlated with nurse stress (r=.70, p < .001) (Heron & Bruk-Lee, 2020). Identifying workarounds can help uncover limitations in available technologies, typical care delivery processes, and physical environments (Litwack, 2018;van der Veen et al, 2020;Yoder-Wise, 2015) but need to be replaced with viable and sustainable innovative solutions (Litwack, 2018).…”
Section: Discussion and Recommendationsmentioning
confidence: 95%